Partisipasi Masyarakat dalam Pengelolaan Mangrove Petengoran sebagai Objek Ekowisata di Desa Gebang Lampung - Zulfahmi Agustiadi; Afrilia Elizabet Sagala (Yayasan Literasi Sains Indonesia, 2024)
Ecotourism is a form of tourism that is responsible for preserving nature, provides economic benefits, and maintains the cultural integrity of local communities. This study used qualitative research methods. Community participation in participating in the management of Petengoran Mangrove ecotourism starts from the decision making stage, implementation stage and monitoring and evaluation stage. Overall, community participation in participating in the management of Petengoran Mangrove ecotourism starting from the decision making stage, implementation stage and monitoring and evaluation stage tends to be in the medium category with a percentage value of 60%. Government participation can be seen from the aspects of financing, implementation of activities and role in the decision-making process. Based on the support of facilities and infrastructure in the Petengoran Mangrove ecotourism, the majority of respondents assessed that the support of existing facilities and infrastructure was classified as high or adequate, namely 87%. Facilities and infrastructure that are classified as high according to respondents are parking facilities, prayer rooms, gazebos, toilets, photo spots. Ease of access is one of the main factors that helps travelers in planning visits to tourist areas.